Earth Observation Applications and the Right to Privacy: Within and Beyond the COVID-19 Pandemic - Yuran Shi (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2022)
Earth Observation (EO) applications interact with many industries and government practices. When EO applications touch upon data being able to identify individuals or certain groups, the processing methods adopted therein entail the balance between public interests in EO applications and the values of privacy protection. It then raises the question of whether and to what extent the EO data comes under privacy protection. This study builds on the methodologies of positive law analysis and normative analysis, with supplementary discussions on the role of EO applications in the COVID-19 pandemic. In recognising the conclusion that the right to privacy entails restrictions on data processing within EO applications, the principle of proportionality calls for solutions to fill the gaps in the regulatory framework. Though legislative solutions are possible in theory, it is not an easy job to get consensus among States in practice. A more appropriate solution lies in introducing a privacy ranking regime internationally, with supplementary enforcement practices on the regional and national levels.